Chemical Composition, Antioxidant Activity and Cytocompatibility of Polyphenolic Compounds Extracted from Food Industry Apple Waste: Potential in Biomedical Application - Parinaz Hobbi; Oseweuba Valentine Okoro; Maryam Hajiabbas; Masoud Hamidi; Lei Nie; Véronique Megalizzi; Paul Musonge; Gianina Dodi; Amin Shavandi (Molecules, 2023)
Apple pomace (AP) from the food industry is a mixture of different fractions containing bioactive polyphenolic compounds. This study provides a systematic approach toward the recovery and evaluation of the physiochemical and biological properties of polyphenolic compounds from AP. We studied subcritical water extraction (SCW) and solvent extraction with ethanol from four different AP fractions of pulp, peel, seed, core, and stem (A), peel (B), seed and core (C), and pulp and peel (D). The subcritical water method at the optimum condition resulted in total polyphenolic compounds (TPC) of 39.08 ± 1.10 mg GAE per g of AP on a dry basis compared to the ethanol extraction with TPC content of 10.78 ± 0.94 mg GAE/g db. Phloridzin, chlorogenic acid, and quercetin were the main identified polyphenolics in the AP fractions using HPLC. DPPH radical scavenging activity of fraction B and subcritical water (SW) extracts showed comparable activity to ascorbic acid while all ethanolic extracts were cytocompatible toward human fibroblast (3T3-L1) and salivary gland acinar cells (NS-SV-AC). Our results indicated that AP is a rich source of polyphenolics with the potential for biomedical applications.